2015
DOI: 10.1007/s00438-015-1144-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and phylogenetic analysis of plant RNA binding proteins comprising both RNA recognition motifs and contiguous glycine residues

Abstract: This study focused on the identification and phylogenetic analysis of glycine-rich RNA binding proteins that contain an RNA recognition motif (RRM)-type RNA binding domain in addition to a region with contiguous glycine residues in representative plant species. In higher plants, glycine-rich proteins with an RRM have met considerable interest as they are responsive to environmental cues and play a role in cold tolerance, pathogen defense, flowering time control, and circadian timekeeping. To identify such RRM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…In addition to RBP45A (AT4G54900), we found multiple members of the family of GLYCINE-RICH PROTEINs, GRP2 (AT14G13850), GRP7 (AT2G21660), and GRP8 (AT4G39260) interacted with this sequence motif (Figures 5A and S4 and Table S4). GRPs are nuclear localized hnRNP-like proteins (Streitner et al, 2012) that are required for numerous processes in plants, including responses to various biotic and abiotic stresses via their function in regulating both alternative splicing and microRNA biogenesis (Lewinski et al, 2016). Therefore, we were unsurprised when we observed that similar levels of GRP7 and GPR8 were present in the nuclei of both root hair and nonhair cells (Figure S6F).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to RBP45A (AT4G54900), we found multiple members of the family of GLYCINE-RICH PROTEINs, GRP2 (AT14G13850), GRP7 (AT2G21660), and GRP8 (AT4G39260) interacted with this sequence motif (Figures 5A and S4 and Table S4). GRPs are nuclear localized hnRNP-like proteins (Streitner et al, 2012) that are required for numerous processes in plants, including responses to various biotic and abiotic stresses via their function in regulating both alternative splicing and microRNA biogenesis (Lewinski et al, 2016). Therefore, we were unsurprised when we observed that similar levels of GRP7 and GPR8 were present in the nuclei of both root hair and nonhair cells (Figure S6F).…”
Section: Resultsmentioning
confidence: 99%
“…An increasing number of RBG genes have been isolated and identified in diverse species, including Arabidopsis thaliana (Arabidopsis) [13][14][15], Oryza sativa [13,14,16], Zea mays [14,17], Brassica rapa [14,18], Ipomoea trifida [19], Gossypium arboreum and Gossypium raimondii [20], Vitis vinifera [21]. In addition to being the first to reveal the Class IVd GRP genes in Arabidopsis and rice, Krishnamurthy screened the whole genomes of Arabidopsis and rice and uncovered more RBG genes (IVa = 7; IVb = 3; IVc = 4; and IVd = 5 in Arabidopsis and IVa = 6; IVb = 2; IVc = 2; and IVd = 4 in rice) than an earlier study (IVa = 8; IVb = 3; and IVc = 2 in Arabidopsis and IVa = 6; IVb = 3; and IVc = 2 in rice) [13,14].…”
Section: Introductionmentioning
confidence: 99%